Judgment of fitness for work in employees with a history of malignant neoplastic disease and exposed to ionizing radiations: evaluation criteria and their application in a case-series study - Taino, Giuseppe; Giroletti, Elio; Delogu, Alberto; Malagò, Giorgia; Corona, Gianluca; Businaro, Jessica; Imbriani, Mauro (La Medicina del Lavoro, 2014)
Introduction: The increase in working age has many epidemiological consequences, one of which is an increased incidence of neoplastic diseases among the working population. Therefore it is more frequent than in the past that the Approved Physician (“Autorizzato” according to Italian legislation) have to judge working fitness in employees suffering from cancer and at the same time exposed to ionizing sources. Aims: In this study we give suggestions for the decision if a worker, who have previously suffered from malignant tumors, is ready to go or not to go back to work. Methods: Though we believe in the preventive theory of the linear correlation without threshold for stochastic effects (“Linear No Threshold” LNT), we considered data from the literature that highlight how very low doses of radiation exposure do not increase the risk of stochastic effects and how the potential occupational exposure to low doses does not introduce a significant additional risk of cancer in subjects with a history of malignant tumor. Results: We identify “objective” elements of judgment related to the neoplastic disease of the worker and his activity, but we emphasize the importance of the psychological condition of the worker, as well as his professional interest and his career opportunities. Conclusions: The criteria we recommend were applied to a group of workers suffering from cancer and with different working activities at risk of exposure to ionizing radiations. The evaluation process is a first rational approach to the assessment of their suitability in worker suffering from neoplastic disease, with the need for custom handling for each individual.